2020
DOI: 10.1088/1757-899x/737/1/012083
|View full text |Cite
|
Sign up to set email alerts
|

Field study of the effect of jet grouting parameters on strength based on tensile and unconfined compressive strength

Abstract: The improvement of the mechanical soil characteristics of jet grouting technique is very attractive. The jet grouted soil cement columns in soft is a complicated issue because it depends on a number of factors such as, soil nature, mixture, influence among soil and grouting materials, jetting force of nozzle, jet grouting and water flow rate, rotation and lifting speed. This paper discusses the estimation of shear strength parameters of soil-cement column (soilcrete) in soft clayey soil based on the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, current investigators have found that the square root correlation between splitting tensile strength and compressive strength is not the best fit for maturing concrete, and the power of compressive strength ranges from 0.6 to 0.8 [33]. [34], and AL-Kinani and Ahmed-2020 [35]).…”
Section: Study Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, current investigators have found that the square root correlation between splitting tensile strength and compressive strength is not the best fit for maturing concrete, and the power of compressive strength ranges from 0.6 to 0.8 [33]. [34], and AL-Kinani and Ahmed-2020 [35]).…”
Section: Study Results and Discussionmentioning
confidence: 95%
“…Figure 10: Mohr-Coulomb Envelope for Mohr circles stress of T and UCS of the injected soil (after Kramadibrata et al-2008[34], and AL-Kinani and Ahmed-2020[35]). …”
mentioning
confidence: 99%
“…There are numerous studies on the stiffness evolution of cement‐treated soils based on laboratory tests or numerical models (Kang et al, 2017; Subramaniam & Banerjee, 2020; Tinoco et al, 2014), but not on in situ tests. It is worth noting that the works based on field tests that study the strength at different times are carried out on test columns (Al Kinani et al, 2020) and allow checking the evolution of the strength after 28 days, so it is not possible to test during the early stages of setting.…”
Section: Introductionmentioning
confidence: 99%